Modification of the existing maximum residue level for folpet in lettuces. (28th April 2022) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; Magrans, Jose Oriol; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Probelte SA submitted a request to the competent national authority in Spain to modify the existing maximum residue levels (MRLs) for the active substance folpet in lettuces. The data submitted in support of the request were found to be sufficient to derive an MRL proposal for lettuces. Adequate analytical methods for enforcement are available to control the residues of folpet and phthalimide in high water content commodities at the validated LOQ values of 0.05 mg/kg for folpet and 0.01 mg/kg for phthalimide. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of folpet according to the reported agricultural practice is unlikely to present a risk to consumer health.